ANALISIS EFEKTIVITAS DAN EFISIENSI PENGELOLAAN DANA PENYERTAAN DESA TERHADAP PENDAPATAN ASLI DESA (PADes) DARI BAGI HASIL USAHA BUMDES (Studi Pada Badan Usaha Milik Desa Di Kecamatan Mananggu Kabupaten Boalemo) - Abdullah, Julie; Hasanuddin, Hasanuddin; Lamuda, Ilyas; Gude, Maksum (Program Studi Akuntansi, 2024)
This study aims to analyze the effectiveness and efficiency of village participation fund management on village original income from business sharing results, focusing on Village-Owned Enterprises (BUMDes) in Mananggu Sub-District, Boalemo Regency. The research method employed is Mixed Method Exploratory Design, integrating both quantitative and qualitative approaches. The research findings indicate that the management of village participation funds in BUMDes in Mananggu Sub-District from 2018 to 2022 is categorized as ineffective and inefficient based on the quantitative approach, with an average effectiveness value of 38.95 and an average efficiency value of 183.4. Qualitative research reveals several factors contributing to the poor management of BUMDes businesses, including low integrity of managers, limited human resource capabilities in managing businesses and identifying market opportunities, as well as the predominant use of participation funds for operational purposes rather than business unit capital development. Moreover, inadequate supervision by the village government, particularly in periodically evaluating managerial performance, also contributes to the low effectiveness and efficiency of village participation fund management.